2016
DOI: 10.1136/archdischild-2015-309190
|View full text |Cite
|
Sign up to set email alerts
|

Skills retention in Sudanese village midwives 1 year following Helping Babies Breathe training

Abstract: VMWs, despite a high illiteracy rate, absorbed and sustained HBB skills for at least a year. Regular, low intensity, manikin-based skills training with peers may have helped sustain FMV, but not hand-cleansing skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…The decline in skills we observed after the first four months is consistent with previous research [9,10]. The most effective method to refresh these skills, however, has yet to be determined.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The decline in skills we observed after the first four months is consistent with previous research [9,10]. The most effective method to refresh these skills, however, has yet to be determined.…”
Section: Discussionsupporting
confidence: 92%
“…A final limitation of this study is that the simulation examinations were administered and scored by four different individuals, without evaluating for inter-rater variation such as in a study from Sudan [10]. However, as the OSCE remains consistent across time and among all study subjects, and all evaluators received the same HBB Master Trainer course, it is not surprising that the Sudanese study found strong inter-rater agreement, and therefore this did not likely significantly alter our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single training sessions have been associated with adequate skills retention [9,34]; however, frequent brief on-site sessions were shown to retain skills as well as improve the clinical outcomes of resuscitated babies [6]. Midwives reported that more practical training would increase their knowledge, skills, competence and confidence in performing ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we showed that a selection of Sudanese VMWs acquired and retained resuscitation skills for up to a year following HBBT plus regular peer–peer skills practice (HBBT +RPPSP ) 16. The purpose of this paper was to present findings related to newborn resuscitation practices, FSB and first-week ENND in the same cohort of VMWs before and after HBBT +RPPSP .…”
Section: Introductionmentioning
confidence: 90%